New Synthesis Method of the Mg2Ni Compound by Using Mechanical Alloying for Hydrogen Storage - H. Suwarno; W. Ari Adi; A. Insani (PPIKSN-BATAN, 2008)
The synthesis and characterization of Mg2Ni compound by using mechanical alloying through wet method have been performed. The Mg2Ni sample was prepared by mixing the Mg and the Ni powders in the media of toluene under argon atmosphere. The mixtures are then milled under the varied milling time of 5, 10, 15, 20, and 25 hours in order to measure the growth of Mg2Ni compound. The X-ray diffraction measurement result showed that both Mg2Ni and MgNi2 crystals could grow well. From the refinement results of the X-ray diffraction pattern using Rietan analysis indicated that the fraction of Mg2Ni and MgNi2 compounds formed are 9.31% and 4.1%, 23.31% and 17.63%, 45.3% and 23.73%, 62.04% and 19.08%, 87.44% and 0.05% for the milling time of 5, 10, 15, 20, and 25 hours, respectively. This result differs from that obtained from the previous research, especially for 25 hours of milling time, the fraction of Mg2Ni and MgNi2 compounds formed were only reach 51.03% and 8.86%, due to the growing of the pollutant phase like MgO. The use of toluene as the media of milling succeeded to remove the growth of the MgO compound.